GEOPOLITICAL RISK, PRICE OF COAL, DAN COAL CASH COST PENGARUHNYA TERHADAP COMPANY VALUE (Penelitian di Perusahaan Sektor Energi Batu Bara yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2023) - Neng Reni Anggia Damayanti; Ade Jamarudin (Laboratorium FEBI UIN SGD Bandung, 2025)
The coal energy sector is highly influenced by geopolitical risks, coal price fluctuations, and production costs. This study aims to analyze the effect of Geopolitical Risk (GPR), Price of Coal (POC), and Coal Cash Cost (CCC) on Price to Book Value (PBV) in Indonesian coal energy companies listed on the Indonesia Stock Exchange (IDX) from 2014 to 2023. Using panel data regression with the Random Effect Model (REM), the results show that GPR negatively and significantly affects PBV, POC positively and significantly affects PBV, while CCC has a negative but insignificant effect. Simultaneously, these variables significantly influence PBV. These findings support Signaling Theory, Commodity Price Theory, and Firm Value Theory and align with previous studies. The study contributes to financial management by providing insights into investment decision-making and risk management in energy companies facing market volatility and geopolitical uncertainty.